168k views
0 votes
H(x)=2x-6/4x^2+8
h(-1)=?

H(x)=2x-6/4x^2+8 h(-1)=?-example-1
User Arrow Cen
by
4.8k points

1 Answer

3 votes

Explanation:

h(-1) simply means that x=-1, and we use that everywhere in the function, where x appears, and simply calculate the result.

that is how a function works. out of an input value (x) we generate/calculate a result value (y).

(2x - 6) / (4x² + 8)

x = -1

(2×-1 - 6) / (4×-1² + 8) = (-2 - 6) / (4×1 + 8) = -8 / (4+8) =

= -8/12 = -2/3

h(-1) = -2/3

User Davelupt
by
4.6k points